Research on the basic theory and application of enhanced recovery in tight sandstone gas reservoirs - Gao Shusheng; Ye Liyou; Liu Huaxun; Zhang Jianzhong; Zhu Wenqing; An Weiguo (Heliyon)
Tight sandstone gas reservoirs are characterized by high water saturation, significant seepage resistance, low single-well productivity, rapid decline, and low gas recovery. Enhancing the recovery rate of tight sandstone gas reservoirs is a complex engineering challenge that necessitates thorough, refined, and systematic research into its fundamental theories. This study employs a comprehensive approach integrating mercury injection, nuclear magnetic resonance, micro-model visualization, and simulation experiments of displacement and inter-layer seepage flow, alongside foundational seepage theories, to systematically explore the characteristics of tight sandstone gas reservoirs, seepage patterns, and methods for improving gas recovery. Our findings reveal: (1) Detailed characterization of the microscopic pore characteristics in tight sandstone reservoirs helps disclose the status and mechanisms of gas-water occurrence and the principal mechanisms of water production under gas-water co-sealing conditions, such as gas expansion, energy of water-sealed gas, movable water volume, and displacement pressure gradient; (2) Testing single-phase and gas-water two-phase seepage characteristics under bound water saturation identifies permeability and water saturation as critical parameters influencing gas seepage characteristics; (3) Inter-layer gas-water interaction flow experiments demonstrate the interference in multi-layer commingled production and introduce the concept of an interference index, a predictive model for well productivity and dynamic performance in the Sulige tight sandstone gas reservoir; (4) A model correlating reservoir recovery rates with drive indices has been developed, highlighting that increasing production pressure differential and reducing seepage resistance are the primary strategies for enhancing recovery rates in tight sandstone gas reservoirs, supplemented by six technological countermeasures including water-blocking, water control, and densifying well networks. The research outcomes provide effective guidance for practical measures to enhance recovery in tight sandstone gas reservoirs.